2015
DOI: 10.1007/s11105-015-0891-9
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Spinach Bacterial Artificial Chromosome (BAC) Library as a Resource for Gene Identification and Marker Development

Abstract: Spinach (Spinacae oleracae) is a nutritious vegetable and an economically important crop worldwide. Spinach is threatened by a number of diseases, and the most significant of which is downy mildew, caused by Peronospora farinosa f. sp. spinaciae (Pfs). The spinach locus RPF1 confers resistance to 11 of the 15 known races of Pfs. To study the RPF1 locus in depth, a BAC library was constructed from DNA of a single spinach plant that was homozygous at the RPF1 locus. The BAC library contained 73,728 clones, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Another study used a set of six SSR markers to investigate genetic diversity in 50 spinach accessions and showed the spinach accessions had high genetic diversity and reported that the accessions from West Asia (Afghanistan, Iran, Iraq, and Syria) had the highest genetic diversity 17 . Furthermore, a search on the bacterial artificial chromosome (BAC) end sequences identified 100 SSR markers showing multiple PCR bands, but the markers were not used to fingerprint or assess diversity 18 . Another study reported a set of 85 polymorphic SSR markers mined from genome sequences of a spinach cultivar, and the loci were genotyped in a set of 48 worldwide spinach accessions and found clustering of spinach accessions based on geographical origin 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Another study used a set of six SSR markers to investigate genetic diversity in 50 spinach accessions and showed the spinach accessions had high genetic diversity and reported that the accessions from West Asia (Afghanistan, Iran, Iraq, and Syria) had the highest genetic diversity 17 . Furthermore, a search on the bacterial artificial chromosome (BAC) end sequences identified 100 SSR markers showing multiple PCR bands, but the markers were not used to fingerprint or assess diversity 18 . Another study reported a set of 85 polymorphic SSR markers mined from genome sequences of a spinach cultivar, and the loci were genotyped in a set of 48 worldwide spinach accessions and found clustering of spinach accessions based on geographical origin 19 .…”
Section: Introductionmentioning
confidence: 99%
“…However, none of the 57,519 SSRs for which primers were designed were tested (Yang et al 2016). Indeed, before NGS sequencing, only 113 spinach-specific SSR markers had been published with only 13 SSR markers used for genetic diversity analysis (Khattak et al 2006(Khattak et al , 2007Feng et al 2015). Thus, the goal of the present work was to develop and test additional SSR markers for use in diversity studies and breeding of spinach and closely related species.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, West Asian accessions (from Afghanistan, Iran, Iraq, and Syria) had the highest level of diversity. Feng et al (2015) designed pairs of primers for 100 SSRs and 24 retrotransposons from BAC end sequences, but did not use the markers to study genetic diversity. Chitwood et al (2016) analyzed population structure and genetic diversity of 288 accessions with 1733 single nucleotide polymorphisms (SNPs) using a genotyping by sequencing (GBS) approach.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of tightly linked markers for each RPF locus against each races of P. effusa will enhance the efficiency and precision of developing downy mildew resistance cultivars. The DNA markers tagged to the downy mildew resistance loci are being developed in spinach (Irish et al, 2008;Feng et al, 2015Feng et al, , 2018a, and the development of functional gene-based markers will ease the pyramiding or stacking of several resistance sources (multiple RPF loci) into a single cultivar. Cultivars with multiple resistant genes may be durably resistant and are attractive options for the spinach industry as the evolution of new races against multiple R genes is less likely to occur (McDonald and Linde, 2002).…”
Section: Downy Mildew Disease Resistancementioning
confidence: 99%
“…The RPF1 locus, governed by a single dominant allele, was mapped to chromosome 3, and a codominant marker DM1 was 1.7 cM from the RPF1 locus (Irish et al, 2008). The P. effusa resistance loci RPF1, RPF2, and RPF3 were mapped to a 1.5 Mb region of chromosome 3, and PCR markers that can distinguish the RPF loci were reported (Feng et al, 2015(Feng et al, , 2018a. The RPF1 locus was further narrowed to a 0.89 Mb region between 0.34 and 1.23 Mb, and the three most likely candidate genes were predicted following protein homology comparison between the resistant and susceptible lines (She et al, 2018).…”
Section: Introductionmentioning
confidence: 99%